Altered insemination timing improves pregnancy rates after a CO-Synch + CIDR protocol - Dobbins, C. A.; Tenhouse, D. E.; Eborn, D. R.; Johnson, Sandra K.; Harmoney, Keith R.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our objective was to determine the optimal time to inseminate lactating beef cows after applying the CO-Synch + CIDR protocol [injection of GnRH given seven days before and 48 to 72 hr after an injection of prostaglandin F2α (PGF2α) concurrent with AI, with a controlled internal drug release (CIDR) insert containing progesterone placed intravaginally for seven days between the first GnRH injection and PGF2α.]. Using 605 beef cows located at three Kansas locations, the CO-Synch + CIDR protocol was administered as follows: an injection of GnRH was given concurrent with a vaginally placed, progesterone-releasing CIDR insert, seven days later the insert was removed, and PGF2α was injected. Blood samples were collected 10 days before initiating the protocol and at the time of GnRH injection and CIDR insertion to determine concentrations of progesterone. Cows in each herd were inseminated at four different times after the PGF2α injection: 48, 56, 64, or 72 hours. At insemination, each cow received a GnRH injection to induce ovulation. Pregnancy was diagnosed at 32 days after insemination and again at 63 days after insemination to confirm pregnancy survival. Pregnancy rates were greatest for those cows inseminated at 56 or 64 hours.
Keywords: Beef; Cattle; CO-Synch; CIDR protocol; A.I.